2013
DOI: 10.1016/j.fct.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and mercury molar ratios in commercial fish from New Jersey and Illinois: Variation within species and relevance to risk communication

Abstract: There is an emerging consensus that people consuming large amounts of fish with selenium:mercury ratios below 1 may be at higher risk from mercury toxicity. As the relative amount of selenium increases compared to mercury, risk may be lowered, but it is unclear how much excess selenium is required. It would be useful if the selenium:mercury ratio was relatively consistent within a species, but this has not been the case in our studies of wild-caught fish. Since most people in developed countries and urban area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 81 publications
(102 reference statements)
3
22
0
Order By: Relevance
“…However, the bioavailability of Se can be sufficiently reduced by Hg to perturb the normal Se-dependent functions (Sørmo et al, 2011). Others have reported that Se/Hg molar ratios below one may lead to a higher risk from Hg toxicity (Ralston and Raymond, 2010;Burger and Gochfeld, 2013). Therefore, the Se/Hg molar ratio is an important piece of information when assessing the health risks from MeHg exposure due to fish consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, the bioavailability of Se can be sufficiently reduced by Hg to perturb the normal Se-dependent functions (Sørmo et al, 2011). Others have reported that Se/Hg molar ratios below one may lead to a higher risk from Hg toxicity (Ralston and Raymond, 2010;Burger and Gochfeld, 2013). Therefore, the Se/Hg molar ratio is an important piece of information when assessing the health risks from MeHg exposure due to fish consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Saltwater fish (including marine and estuarine species) were collected from New Jersey (2003-2011) (57,99,100) and from the Aleutians in Alaska (2003-2005) (101). Freshwater fish were collected from South Carolina (1997-1998) (102) and Tennessee (103).…”
Section: Methodsmentioning
confidence: 99%
“…Freshwater fish were collected from South Carolina (1997-1998) (102) and Tennessee (103). Commercial fish were purchased in New Jersey (2003)(2004) (104) and Illinois (2004) (57,105), and canned tuna and tuna sushi were purchased in New York and New Jersey (1998-2004) (106). Freshwater and saltwater samples were collected from fishermen or by state personnel under our direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have also presented evidence of the nutritional benefits of selenium (Se), also commonly found in fish (Cabanero et al, 2005;Burger et al, 2011;Burger and Gochfeld, 2013). In addition to the benefits of Se as an antioxidant and for disease prevention, this element has been examined with respect to counteracting the adverse effects of Hg (Burger et al, 2011: Carvalho et al, 2012Cuvin-Aralar and Furness, 1991;Ralston and Raymond, 2010;Watanabe, 2002).…”
mentioning
confidence: 99%